PENGEMBANGAN UMKM MASYARAKAT BANDUNG - Anwar, Husen Saeful (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
This article examines Western thought in formatting social order based on rasionalism, empiricism, and church. This discussion is significant in tracing the origins on social doctrin in the modern social-ethical system. By bibliographical literatur from classical books, this study describes and analyzes what are being formated in Classical and Medieval Western Tradition about social justice. By that tradition, it is clear that West has tradition of individualism as well as communalism. Both of  classical section have being referenced in the world.